Red Tail Captured, Red Tail Free : Memoirs of a Tuskegee Airman and POW, Revised Edition - Jefferson, Alexander, 1921-; Carlson, Lewis H. (World War II--the global, human, and ethical dimension., 2017)
Red Tail Captured, Red Tail Free is a rare gift detailing the experience of Lt. Col. Alexander Jefferson, who was one of 32 Tuskegee Airmen from the 332nd Fighter Group to be shot down defending a country that considered them to be second-class citizens. In this vividly detailed, deeply personal story, Jefferson writes as a genuine American hero about what it meant to be an African American pilot in enemy hands, fighting to protect the promise of freedom. The book features the sketches, drawings, and other illustrations Jefferson created during his nine months as a POW, and Lewis Carlson's authoritative background to the man, his unit, and the fight Alexander Jefferson fought so well. This revised edition covers the story of Jefferson's continuing outreach and education work, as he brings the story of the Tuskegee Airmen to communities and schools across the country, and the presentation of the Congressional Gold Medal to the Airmen in 2007. Red Tail Captured, Red Tail Free is perhaps the only account of the African American experience in a German prison camp.